Hierarki Kebutuhan Tokoh Utama dalam Novel Mariposa Karya Luluk HF - Selsa Dwi Agustiyani; Putri Khasanah; Eva Dwi Kurniawan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The aim of this research is to describe the hierarchy of needs experienced by the main character in the novel Mariposa by Luluk HF. The method in this research uses a descriptive qualitative method, which describes data through sentences, phrases and clauses. The data in this research is in the form of words or groups of words, not numbers. The approach used in this research is using a literary psychology approach with Abraham Maslow's hierarchy of needs theory. It can be concluded that in the novel Mariposa by Luluk HF, various forms of fulfilling needs are found by the main character.